Privacy Enhancing Technologies 8th International Symposium, PETS 2008 Leuven, Belgium, July 23-25, 2008 Proceedings - Borisov, Nikita.; Borisov, Nikita.; Goldberg, Ian.; Goldberg, Ian. (Security and Cryptology, 2008)
This book constitutes the thoroughly refereed post-proceedings of the 8th International Symposium on Privacy Enhancing Technologies, PET 2008, held in Leuven, Belgium, in July 2008 in conjunction with WOTE 2008, the IAVoSS Workshop on Trustworthy Elections. The 13 revised full papers presented were carefully selected from 48 submissions during two rounds of reviewing and improvement. The papers - both from academia and industry - cover design and realization of privacy services for the internet and other communication networks and present novel research on all theoretical and practical aspects of privacy technologies, as well as experimental studies of fielded systems. .